Rencana Pengembangan Kawasan Mangrove Setapuk Kecamatan Singkawang Utara - Maria Louise Fita; Jasisca Meirany; Mochammad Meddy Danial (Departemen Teknik Kelautan Universitas Hasanuddin, 2023)
The Setapuk mangrove area is located in North Singkawang District. The distance of the mangrove area from Singkawang city center is around 10 km with 20-minute travel times. Currently, the function of the mangrove area is to become the Center for Coastal Ecosystem Restoration and Development as well as a place for education, research, and a natural laboratory. However, currently, the tourist attractions in the Mangrove Setapuk area are still lacking in diversity. Apart from that, photo spots in the area are still very minimal and lacking in variety, so this research was carried out to determine the potential of the Setapuk mangrove area and plan its development as a tourist area. The research method used is a qualitative descriptive method with the SWOT analysis method. The Setapuk mangrove area development plan was formulated through IFAS and EFAS analysis and then continued by determining the Grand Strategy Matrix where the analysis showed that the Setapuk mangrove area was in quadrant I with values x=0.32 and y=0.27. The strategy that can be used to develop the Setapuk mangrove area is the S-O strategy, namely by using the strengths that they have and taking advantage of the best existing opportunities. Meanwhile, the recommended strategy that can be implemented in the Setapuk mangrove area is progressive and supports aggressive growth policies.